To find the convergence of the series `sum_(n=2)^oo 1/(n(ln(n))^p) ` where `pgt0` (positive values of `p` ), we may apply integral test.

**Integral test** is applicable if f is *positive, continuous, and decreasing function* on an interval and let `a_n=f(x)` . Then the infinite series` sum_(n=1)^oo a_n` converges if and only...

## Get

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

To find the convergence of the series `sum_(n=2)^oo 1/(n(ln(n))^p) ` where `pgt0` (positive values of `p` ), we may apply integral test.

**Integral test** is applicable if f is *positive, continuous, and decreasing function* on an interval and let `a_n=f(x)` . Then the infinite series` sum_(n=1)^oo a_n` converges if and only if the improper integral `int_1^oo f(x) dx ` converges to a real number. If the integral diverges then the series also diverges.

For the infinte series series `sum_(n=2)^oo 1/(n(ln(n))^p)` , we have:

`a_n =1/(n(ln(n))^p)`

Then,` f(x) =1/(x(ln(x))^p).`

The `f(x)` satisfies the conditions for integral test based on the following reasons:

-` f(x)` is continuous since` x(ln(x))^p !=0` for any x-value on the interval `[2,oo)`

-` f(x)` is positive since `1/(x(ln(x))^p)gt0 ` for any x-value on the interval `[2,oo).`

-` f(x)` is decreasing since `f'(x)` is negative for large value of `x` . It eventually decreases at the tail of the series.

To evaluate the convergence of the series using integral test, we set-up the improper integral as:

`int_2^oo 1/(x(ln(x))^p)dx`

Apply u-substitution by letting: `u=ln(x)` `u=ln(x)` then `du = 1/xdx` , `a=ln(2)` and `b=oo` .

`int_(ln(2))^oo 1/(x(ln(x))^p) dx=int_(ln(2))^oo 1/(ln(x))^p *1/xdx`

`= int_(ln(2))^oo 1/u^pdu`

` =int_(ln(2))^oo u^-p dx`

`= u^(-p+1)/(-p+1)|_(ln(2))^oo `

`=u^(-(p-1))/(-p+1)|_(ln(2))^oo`

`=1/(u^(p-1)(-p+1))|_(ln(2))^oo`

Apply definite integral formula: ` F(x)|a^b = F(b)-F(a)` .

`1/(u^(p-1)(-p+1))|_(ln(2))^oo=1/(oo^(p-1)(-p+1))-1/((ln(2))^(p-1)(-p+1))`

`= 1/oo-1/(-p+1)1/(ln(2))^(p-1)`

` =0-1/(-p+1)1/(ln(2))^(p-1)`

` =1/(-p+1)1/(ln(2))^(p-1)`

The integral converges to a real number when `pgt1` .

Thus, the series `sum_(n=2)^oo 1/(n(ln(n))^p)` converges whenever `pgt1` .